Recessively inherited costovertebral segmentation defect with mesomelia and peculiar facies (Covesdem syndrome): A new genetic entity? - Wadia, R S (1978)
Two sibs of a consanguineous mating are described. Both have a gross costovertebral segmentation defect affecting nearly all the thoracic vertebrae, and mesomelia of the limbs, with the upper limbs being obviously more affected than the lower. The facial appearances of the two are identical, with hypertelorism, depressed nasal bridge, large bony upper lip, constantly open mouth, and peg-like teeth. We believe this combination has not been described before and represents the effect of a 'new' recessive gene. We would like to name this combination Covesdem syndrome (costovertebral segmentation defect with mesomelia).